Centrifugal empire : central-local relations in China - Chŏng, Chae-ho, 1960- (Columbia University Press, 2016)
Despite the destabilizing pull of a vast territory and a large multicultural population, the centralized government of the People's Republic of China has held together for decades, resisting efforts at local autonomy. By examining Beijing's strategies for maintaining control even in the reformist post-Mao era, Centrifugal Empire reveals the unique thinking behind China's approach to local governance, its historical roots, and its deflection of divergent interests. Centrifugal Empire examines the logic, mode, and instrument of local governance established by the People's Republic, and then compares the current system to the practices of its dynastic predecessors. The result is an expansive portrait of Chinese leaders' attitudes toward regional threats and local challenges, heightened by territory-specific preoccupations and manifesting in constant searches for an optimal design of control. The book reveals how communist instruments of local governance echo imperial institutions, while exposing the Leninist regime's savvy adaptation to contemporary problems and underscoring the need for more sophisticated inter-local networks to keep its unitary rule intact. It understands the challenges to China's central-local relations as perennial, since the dilution of the system's "socialist" or "Communist" character will only accentuate its fundamentally Chinese'or centrifugal'nature